(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The city represents one of the most significant achievements of human civilization, serving as a practical outcome of the interaction between social and economic values on the one hand, and natural factors on the other. As such, the city has become a complex and dynamic phenomenon with multiple dimensions, where its form and structure act as a physical manifestation of these factors. Religious cities exemplify this interaction. The patterns and structures of land use in religious cities quickly respond to the essential factors and values necessary for life. The interaction of these factors and values creates a level of life requirements and sustainability, which we refer to as a "lifestyle" or "way of life." This necessitates that master plans for land use in the city align and respond to the needs of its inhabitants. Religious cities, including Najaf Al-Ashraf as a case study, face unique challenges in planning and design. These challenges stem from their significance, the concentration of their buildings and areas of religious, cultural, and commercial importance—particularly the holy shrines—and the surrounding environmental conditions. All of this highlights the need for specialized studies and plans that are translated into distinct land-use strategies for such cities. Revitalizing our religious cities fundamentally relies on planning them according to sound scientific principles and proper urban planning methodologies.